Probabilistic landslide risk assessment: Case study of Bujumbura - Shirambere, Gervais; Nyadawa, Maurice O.; Masekanya, Jean pierre; Nyomboi, Timothy (My University, 2018)
A spatial probabilistic landslide risk assessment and mapping model has been applied in a data scare region. The probabilistic model is based on a physical model based on Mohr coulomb failure criterion. A Monte Carlo simulation technique is applied to field collected data. The results are integrated and a probability of landslide is obtained at each cell level. The results are compared to a prepared landslide inventory. The overall accuracy of the model is 79.69%.